WAYS TO CREATE SAFE AND HARMFUL WORKING CONDITIONS - Rayimkulov Akhmat; Raimov U.B , (European Journal of Life Safety and Stability (2660-9630), 2021)
The article contains an analysis and recommendations on the main ways to create safe and harmless working conditions, the observance of the legal relationship between employer and employee today.